Perbaikan Kualitas Air dalam Pemanfaatan Mata Air Dusun Kapuhan - Euanggelion Rei Rahardja; Anastasia Yunika (Jurnal Atma Inovasia, 2026)
Water quality is one of the key aspects of both individual and communal clean water supply systems and plays an important role in public health. Kapuhan Hamlet faces challenges related to the quantity, quality, accessibility, and continuity of its clean water supply system. Although efforts have been made to improve the system in order to address issues of quantity, accessibility, and continuity, the potential for contamination remains a concern. This community service project aims to analyze the quality of spring water in Kapuhan Hamlet and identify potential improvement measures. The methods used included laboratory testing of water samples for physical, chemical, and microbiological parameters. The microbiological test results showed that the water samples contained Escherichia coli and total coliform levels exceeding the established quality standards. These findings indicate the need for interventions to improve water quality for the health and safety of users. Based on the analysis results, it can be concluded that although issues related to water quantity, accessibility, and continuity have been addressed, efforts to improve water quality remain essential to ensure the availability of safe and healthy drinking water for the community.